Analisis Strategi Pemasaran Bisnis Mixue dan Teh di Indonesia - Pujiastuti, Dewi; Nuraeni, Kharisna Ajeng; Maylani, Linda; Aidiahsari, Sabrina (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
In this context, the author discusses the analysis of Mixue's business marketing strategy in Indonesia. Mixue is one of the ice cream and tea producers that continues to develop and expand its business in Indonesia. Mixue ice cream and tea is a company engaged in the sales of ice cream and chinese tea that has been operating since 1997, founded by Zhang Hongchao. Mixue's marketing strategy includes low prices, targeting the lower market segment and social media marketing. The purpose of this study is to find out the marketing strategy of mixue companies in the implementation of the business expansion process in Indonesia. The research method used is a qualitative method, the data source is secondary data, the data collection method is articles, journals, the internet and books, then the material is presented descriptively. The results of the study show that Mixue ice cream and tea has succeeded in creating a profitable business for both the parent company and the recipient of the profit certificate, thus making it one of the culinary industry players in Indonesia.